Axis-switching and breakup of rectangular liquid jets. (May 2020) - Morad, Mohammad Reza; Nasiri, Mahdi; Amini, Ghobad
Highlights: The evolution and disintegration of liquids jets ejecting from different rectangular orifices under various operating conditions were studied systematically. Using a direct numerical solution and an adaptive meshing technique, the Navier–Stokes equations with a moving boundary have been solved for the two-phase flow problem. The axis-switching, instability, and breakup of unperturbed and perturbed liquid jets in Rayleigh regime were investigated and the results were compared with experimental measurements and the linear stability analysis predictions. Accounting for disturbances introduced to the jet for a wide range of wavenumbers and amplitudes, the effects of orifice geometry and inlet velocity are investigated. Abstract: The behavior of low-speed liquid jets emerging from rectangular orifices into a quiescent air is studied numerically. After ejection, the rectangular cross-section transforms into an elliptical form along the jet and while axis-switching includes elliptical cross-sections only, the rectangular shape never establishes again. The optimum wavenumber, corresponding to the most dominant wave, is found to be greater in orifices with higher aspect ratios and, as a result, breakup length of the jet will be shorter. The breakup length decreases exponentially with the initial amplitude of disturbances. Moreover, it is observed that the form of final breakup leads to elimination of the satellite droplets at the optimum wavenumber with small and uniform main droplets. It is also shown that high-aspect ratio jets have a more extended range of effective disturbances. The results provide an in-depth insight into the effect of instabilities on axis-switching, breakup, and droplet formation.